2016
DOI: 10.1109/tmi.2016.2526631
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Variant Resolution Modelling for Iterative List-Mode PET Reconstruction

Abstract: A spatially variant resolution modelling technique is presented which estimates the system matrix on-the-fly during iterative list-mode reconstruction. This is achieved by redistributing the endpoints of each list-mode event according to derived probability density functions describing the detector response function and photon acollinearity, at each iteration during the reconstruction. Positron range is modelled using an image-based convolution. When applying this technique it is shown that the maximum-likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We used a spatially invariant kernel for resolution modelling which is optimal at the centre (Angelis et al 2015). A spatially variant kernel (Bickell et al 2016 provide further improvement but we have not investigated this. Regarding noise, the inter-voxel variance of a uniform ROI certainly increases as a function of the duration of the tracking gap or loss of counts, however we have also observed that bias remains <0.5% even when the decrease in counts is >90% (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We used a spatially invariant kernel for resolution modelling which is optimal at the centre (Angelis et al 2015). A spatially variant kernel (Bickell et al 2016 provide further improvement but we have not investigated this. Regarding noise, the inter-voxel variance of a uniform ROI certainly increases as a function of the duration of the tracking gap or loss of counts, however we have also observed that bias remains <0.5% even when the decrease in counts is >90% (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The PSF has to be sampled using the reconstructed image voxel size. To do so, instead of transforming the PSF using (6), as suggested in the derivation of the resolution model in (9), it is more convenient to transform the image space to the scanner space using the inverse transformation of (6). Then, the PSF can be sampled according to the image space sampling size at the corresponding scanner position.…”
Section: ) Calculation Of the Motion Dependent And Spatially Variantmentioning
confidence: 99%
“…More realistic representations consider models which can capture the spatially variant and asymmetric shape of the true PSF [7], [8] usually observed in PET scanners. In addition, the resolution model can be implemented in the projection space [9] or in the image space [3]. However, there is minimal difference in image quality between implementation of both methods [4].…”
mentioning
confidence: 99%
“…Since for listmode reconstruction no sinograms are calculated, an alternative to incorporate the resolution model in the projection space consists on repositioning the LORs according to the probable LOR position calculated from the resolution model. However, this approach has been shown to not perform well using ML-EM listmode reconstruction (Bickell et al 2016). On the other hand, resolution modelling in the image space can be easily adapted for ML-EM list-mode reconstruction, showing good image quality (Cloquet et al 2010), and in practice is easier to adapt than the projection space approach.…”
Section: Introductionmentioning
confidence: 99%